Pendampingan Pemanfaatan Laboratorium Virtual PhET Energy Skate Park pada Pembelajaran Fisika Kelas X di MAN 1 Mataram - Hayatun Novi Aulia; Fadillah Deswita Sari; Lindawati Lindawati; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Education and Community Services, 2026)
Physics learning is often considered difficult by students because it contains many abstract concepts and complex formulas, especially in the topic of work and energy. One effort to help students understand these concepts is through the utilization of virtual laboratories based on PhET (Physics Education Technology) interactive simulations. This community service activity aimed to assist tenth-grade students of MAN 1 Mataram in utilizing the PhET Energy Skate Park virtual laboratory in physics learning. The method used was learning assistance through group discussions supported by student worksheets (LKPD) based on virtual simulations. The activity began with an introduction to the PhET simulation, followed by virtual practicum activities using LKPD and evaluation through observation of student activities and group discussion results. The results showed that students were able to use the PhET simulation effectively and demonstrated high enthusiasm throughout the learning process. The virtual simulation helped students understand the relationship between kinetic energy, potential energy, and mechanical energy through interactive visualization. In addition, the activity increased student engagement in group discussions and learning activities. Therefore, the utilization of the PhET Energy Skate Park virtual laboratory can serve as an effective alternative learning medium to support physics learning on the topic of work and energy.